Overseas Parent Company Revenue Becomes Permanent Establishment Taxable Income in Indonesia - Muhammad Rifky Santoso (International Journal of Applied Business and International Management, 2021)
The tax authority performs tax audits to increase revenue and ensure that taxpayers carry out their tax obligations properly. During the tax audit, there could be a dispute between the taxpayers and the tax authority in interpreting the tax treaty. This paper discusses the dispute over the results of the tax audit conducted by the tax authorities. By using the method of tax court cases in Indonesia, the interpretation of the tax treaty between Indonesian and China cannot be based solely on text. Other sources are needed, such as the UN model and its commentary, and the domestic income tax regulations of the source country. Using some materials to interpret the treaty can prevent tax reduction and tax evasion. The results found that the tax treaty between Indonesian and China only mentions the tax credit method to avoid double taxation, whereas in this case, it is better to use the tax exemption method to avoid double taxation.